(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The land conflict became an urgent problem in the early twentieth century. The Kazakh society had different positions on this issue, and the Kazakh intelligence held different views on the land conflict. At that time, the Kazakh society did not have clear mechanisms for resolving the land conflict, however, there were various proposals and attempts to resolve this issue. The colonial policy of the tsarist Russian Empire intensified the land dispute in Kazakh society. For the first time in the Kazakh society, the issues of renting and selling land began to arise. This led to an aggravation of the land conflict. The issue of renting and selling land was decided by the landowners at their own will, when renting land, some peasants had the question of being unable to get money for rent and even lose their land by renting out land. After the Shcherbina expedition, which caused an aggravation of the land conflict in the Kazakh society, a list of surplus lands was published. This, in turn, led to the transfer of excess land to the state balance sheet. And this issue has led to an even greater increase in the land conflict in the Kazakh society. On these three issues, the Kazakh intelligence had different opinions, they tried to show different ways to resolve the dispute. For example, the position of the newspaper "Kazak" and the magazine "Aikap" on the land conflict was different. We consider the presence of such two different positions as a regularity. In the course of the study, these positions were studied using the methods of comparative and system analysis. Keywords: land conflict, land issue, Kazakh intelligence, conflictology, principles, opinions, Shcherbin’s expedition, land lease, land sale, protest.